To What Extent Can Orbital Cellulitis Emergency Aspect Influence the Diagnosis of Maxillary Sinus Lymphoma? - Yousra Ajhoun; Ismail Aissa; Taoufik Abdellaoui; Yasmine Chaoui Roqai; Ilias Benchafai; Redouan Messaoudi; Rachid Zerrouk; Karim Reda; Abdelbarre Oubaaz (Case Reports in Ophthalmological Medicine)
We present a case of a 46-year-old woman admitted to the emergency department for acute swelling and erythema of the right eyelid for 3 days. Ophthalmological examination was notable for 10/10, P2 best visual acuity, and inflammatory periorbital edema, without exophthalmia nor extraocular motility disturbance. Intraocular pressure was 14 mmHg and fundoscopic examination was not notable for any abnormality. Preseptal cellulitis diagnosis was made, and oral antibiotherapy was immediately started; after 72 hours, the patient did not improve and started complaining of pain on ocular movements. Brain and orbit MRI scan revealed right retroseptal cellulitis associated with homolateral pansinusitis. Intravenous antibiotherapy with oral corticosteroid was started simultaneously leading to full remission but with steroid dependency; 5 days after finishing prednisone, orbital cellulitis symptoms reappeared. The same treatment protocol was given but with corticosteroid tapering over weeks. Nevertheless, steroid dependency persisted. Except for the inflammatory syndrome, complete biological examinations did not disclose any abnormalities. The patient underwent maxillary sinus and fat orbital biopsy; however, histopathological examination was not contributory. Persistence of steroid dependency, chronic atypical rhinosinusitis, normal paraclinical investigations, and age of patient let us suspect lymphoma origin hidden by chronic corticosteroid. We carried out for the second time a maxillary sinus biopsy after stopping steroids, which disclosed primitive non-Hodgkin lymphoma of the maxillary sinus. The aim of this observation is firstly to evoke though it is exceptional the diagnosis of maxillary lymphoma in case of atypical orbital cellulitis and secondly to incite clinicians to be more vigilant in prescribing corticosteroid even if there is an emergency character of orbital cellulitis.